The Role Of Investor Protection And Corporate Governance In Mitigating Insider Trading - Lye, Chun Teck (2017)
Despite the efforts of governments to strengthen and enforce the investor protection laws, insider trading is still evident as insiders have been shown to counteract using new and more sophisticated trading methods to camouflage their actions. Although this study does not deny the effectiveness of legal protection, an exploration of other potential mechanisms that could reinforce the function of investor protection in alleviating insider trading is still worthwhile. Therefore, this study aims to examine the underlying effects of country-level investor protection and corporate governance mechanisms (firm-level corporate governance, product market competition, and financial leverage) on insider trading. On top of a series of diagnostic tests and remedial approaches, this study also addresses the potential endogeneity and persistent insider trading issues by using the two-stage least squares and the dynamic generalized method of moments estimators.